Jolly Joker Dwarfs, Pretty Dolls, and disguised demons in modern persian literature: A close reading of Houshang Golshiri's "Arusak-e Chini-ye Man" (My China Doll) - Kaya, N. (Peter Lang AG, 2022)
[No abstract available]